ACTIVITY STUDY OF BINAHONG (ANREDERA CORDIFOLIA (TENORE) STEENIS) LEAVES WATER EXTRACT ON WISTAR RATS AS ANTI-ULCER PREVENTIVELY AND CURATIVELY - Ulfah, Maria
Background: Binahong (Anredera cordifolia (Tenore) Steenis) leaves has long been used by the community for the treatment of peptic ulcers. This study aims to assess the anti-ulcer activity of binahong leaves with alcohol-induced rats model. Method: Testing of anti-ulcer activity was divided into two steps ie preventive anti-ulcer activity and curative anti-ulcer activity. In both methods above, the animals were divided into eight groups,including normal group, control group: infuseof binahong leavesand boiledbinahong leaves groups with a doses of 50, 100, and 200 mg / kg bodyweight. In anti-ulcer preventive activity test, the animals were fasted for 18 hours but free access to drink. After one hour received the test substances, all groupsexcept the normal group were given alcohol 5 mL / kg body weight orally. After 4 hours, the animals were sacrificed and observed for ulcer. In anti-ulcer curative activity test, the animals were given test substance at doses mentionedabove orally for three days.On day four all treatment groups except the normal group was given alcohol 5 mL / kg body weight orally for two days. On day six the animals were sacrificed after fasted for 18 hours and then observed further. Activities anti-ulcer checked by looking at parameters such as pH of the stomach, the number of ulcers, the severity of ulcers, ulcer index, andpercentage of ulcer inhibition. The data obtained were statistically analyzed using ANOVA and further tested using LSD (Least Significant Difference). Results:Preventive test showed that ulcer index of binahong leaves infuse at doses of 50, 100, and 200 mg / kg bodyweightwere 18; 18.67; and 20.66. The ulcer index ofboiledbinahong leavesatdoses of 50, 100, and 200 mg / kg bodyweightwere 20.66; 16.66; and 15.67 respectively. The percentage inhibition of in binahong leaves infuse at doses of 50, 100 and 200 mg / kg body weight were 18.18%; 15.14%; 19.86%. The ulcer inhibition percentage of boiledbinahong leaves at doses of 50, 100, and 200 mg / kg body weight were 6.09%; 24.27%; 28.77% respectively.Preventive test showed that ulcer index of binahong leaves infuse at doses of 50, 100, and 200 mg / kg bodyweightwere10.01; 5.99; and 5.99. The ulcer inhibition percentage of binahong leaves infuse at dosesof 50, 100, and 200 mg / kg body weight were 63.23%; 36.58%; 63.23% respectively.The ulcer inhibition percentage of boildbinahong leaves at doses of 50, 100, and 200 mg / kg body weight were 38.61%; 63.21%; 63.21% respectively. Conclusion: Binahong leaves water extract showed antiulcer activity either preventivelyor curatively.